Assessing the efficacy of a specific physiotherapy intervention for the prevention of low back pain in female adolescent rowers: a field study - Thorpe, Alison. (Curtin University, 2009)
Objectives: To determine the efficacy of a specific physiotherapy intervention administered to adolescent female rowers with the aim to decrease the prevalence of low back pain (LBP) and associated levels of pain and disability. A secondary aim of the study was to determine whether changes in lower limb endurance and flexibility were evident in an experimental group.Design: A non randomized controlled trial in adolescent female rowers with and without LBP.Setting: Curtin University of Technology, Western Australia and the participating private school boatshed, Perth, Western Australia.Participants: Participants were 82 adolescent female rowers, with and without LBP. These participants attended the same school and were aged between 13-17 years [experimental group 13.9(0.9) years, control group 13.8(1.0) years]Main Outcome Measures: Primary outcome measures in this study included; LBP point prevalence, pain intensity (utilizing a visual analogue scale) and disability level (utilizing a modified Oswestry questionnaire). These measures were taken at four time points over the rowing season. Secondary outcome measures of lower limb flexibility (sit and reach test) and lower limb endurance (timed squat test) were taken in the experimental group only.Results: The experimental group demonstrated a significant reduction in the prevalence of LBP across the rowing season 48% to 19% pre-season to midseason and from 48% to 24% pre-season to end-season. The prevalence of LBP in the control group slightly increased from 22% to 25% pre-season to mid-IV season and was unchanged at 22% pre-season to end-season. A significant increase in the proportion of subjects pain-free was shown in the experimental group at mid-season compared with pre-season (p=0.007), but no change thereafter (p>0.05). In the control group the proportion pain-free remained relatively stable across the four time points (p>O.2 for changes between consecutive times). The experimental group rowers demonstrated reduced pain intensity over the course of the rowing season compared with the control group [mean pre-end season exp 6.4(21.0), control -2.7(17.6) Z= -2.283, P = 0.022]. Levels of disability did not differ between the groups across the rowing season. Significant improvements in lower limb endurance and flexibility were observed in the experimental group (p=<0.05).Conclusions: A specific physiotherapy exercise intervention was effective in reducing the prevalence of LBP in a population of adolescent female rowers and reducing pain intensity levels in subjects who complained of LBP at the commencement of the rowing season. A randomized trial to test the intervention under more rigorous scientific conditions is recommended.